2017
DOI: 10.1007/s40801-016-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Positive Metastatic Breast Cancer Patients Receiving Pertuzumab in a Community Oncology Practice Setting: Treatment Patterns and Outcomes

Abstract: BackgroundPertuzumab (Perjeta®), a HER2/neu receptor antagonist, was approved by the US Food and Drug Administration in June 2012 for use in the first-line setting for patients with HER2-positive metastatic breast cancer (mBC).ObjectiveThis retrospective study investigated the clinical and demographic characteristics, treatment patterns, safety, and clinical outcomes for patients with HER2-positive mBC who received pertuzumab in the first-line setting in US community oncology practices.MethodsPatients with HER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…PERUSE findings complement results from the CLEOPATRA trial, indicating that findings from a phase III trial can be replicated in the routine clinical practice setting. The results also expand upon recently published retrospective and real-world studies of patients treated with pertuzumab, trastuzumab and the investigator's chosen taxane in the United States, Italy and Turkey, which reported median PFS ranging from 17 to 29 months [14][15][16][17]. Strengths of PERUSE results compared with previous reports include the prospective nature of the study, the larger proportion of patients treated with paclitaxel instead of docetaxel, the more rigorous data collection and the regular schedule of tumour assessment according to RECIST (version 1.1).…”
Section: Discussionsupporting
confidence: 79%
“…PERUSE findings complement results from the CLEOPATRA trial, indicating that findings from a phase III trial can be replicated in the routine clinical practice setting. The results also expand upon recently published retrospective and real-world studies of patients treated with pertuzumab, trastuzumab and the investigator's chosen taxane in the United States, Italy and Turkey, which reported median PFS ranging from 17 to 29 months [14][15][16][17]. Strengths of PERUSE results compared with previous reports include the prospective nature of the study, the larger proportion of patients treated with paclitaxel instead of docetaxel, the more rigorous data collection and the regular schedule of tumour assessment according to RECIST (version 1.1).…”
Section: Discussionsupporting
confidence: 79%
“…The most frequent side effects in our study were fatigue and arthralgia/myalgia, with the rates of 75% and 64.3, respectively compared to 37.6% and 15% in CLEOPATRA, 26% and 6% in a retrospective analysis by Placido et al, respectively (12,17). In our study, neuropathy occurred in 8 (28.6%) patients, with the 5 (17.8%) of them being grade 3 compared to 11 (2.7%) patients in CLEOPATRA phase III trial, 60 (18.4%) patients in a retrospective analysis by Esin et al, and 89 (33.5%) patients in another study including 266 patients (18,19). As compared with literature, hematological side effects in our study were observed to be relatively at low rates, with 3 (10.7%) of the patients experiencing grade 1 thrombocytopenia compared to 25 (7.8%) of those in the study by Esin et al, with only 3 of them being grade 3-4 (19).…”
Section: Discussionsupporting
confidence: 48%
“…This rate was only 1% in NEOSPHERE trial that investigated the efficacy of pertuzumab in neoadjuvant setting. In a retrospective study by Robert et al, 2 (0.8%) patients had Left Ventricular Dysfunction (LVD), whereas 8 (2.5%) patients experienced LVD in the study by Esin et al (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 98%
“…Other groups have looked at local or regional tethered observational data regarding efficacy of dual HER2 blockade. A real-world study from 2017 found a mPFS of 16.9 months among 266 patients with HER2-positive mBC receiving first-line trastuzumab and pertuzumab [ 13 ]. The majority of patients (n = 249) received a taxane as the chemotherapy-backbone.…”
Section: Discussionmentioning
confidence: 99%